Feelings in psychological perspective. Issue 1 (2nd January 2017) - Hayes, Linda J.; Fryling, Mitch J.
ABSTRACT: Based upon B. F. Skinner's Radical Behaviorism, feelings are most often considered to be private events by behavior analysts, constituting biological happenings. This paper describes conceptual issues with the Skinner's public–private dichotomy, considering the organismic participant, the relational property of psychological events, the concept of the whole organism, and the environmental participant. After considering these issues, practical problems related to the public–private dichotomy are considered, and finally, an interbehavioral alternative to the conceptualization of feeling events is proposed. The distinguishing features of feeling events relative to other psychological events are highlighted.